Bridging and bonding social capital for sustainable technology adoption, the Landcare program in the resource poor rural town of Claveria, Philippines - Rodmyr F. Datoon; Jose V. Camacho Junior; Aileen V. Lapitan; Jeanarah M. Gapas (Research in Globalization, 2023)
The important role of bonding and bridging social capital in technology adoption has been well documented. This holds true in the dissemination of soil conservation technologies in the town of Claveria under the Landcare program. Past studies unanimously attribute high adoption rates to the formation of farmer Landcare groups, which is a form of bonding social capital, and to the provision of human and physical resources through external networks, a form of bridging social capital. After more than 20 years since the project ended in the town, this study unpacks this relationship and illustrates how the two types of social capital are complementary for sustained technology adoption. Data from household surveys, focus group discussions, and key informant interviews illustrate that the training and physical resources provided through external organizations and partnerships greatly contributed to program participation and high adoption rates of technologies. When such external organizations left the town, adoption rates fell and some farmers reverted to their traditional farm practices. These findings contribute to the debate on the complementation of the two types of social capital in sustaining adoption as well as illustrate how the two types relate to each other for sustainable rural development programs.
Keywords: 330; Bonding social capital; Bridging social capital; Landcare program; Philippines; Soil conservation